The New And Multi-Faceted Dimensions Of Articles 5 And 8 Of The Federal Constitution In The Control Of Administrative Action - C.K.G. Pillay, Sudha d/o (Journal of Malaysian and Comparative Law, 1999)
Of late, administrative law in Malaysia has witnessed a tremendous spurt of judicial activity. A distinct change in judicial policy on matters pertaining to public law may be discerned from the recent decisions. The courts are making a determined and conscious effort to break away from a slavish adherence to the common law in England and looking instead to the constitutional principles enshrined in the Federal Constitution for guidance in resolving disputes between the individual and the administration. In particular, a fresh breath of life has been infused into articles 5 and 8 of the Federal Constitution and both articles have now become important weapons in the artillery of the judiciary to control the abuse of administrative power. The purpose of this paper is to examine the new and multi-faceted dimensions that have been given to articles 5 and 8 of the Federal Constitution.